Transurethral cystolithotripsy in gas (CO2) medium - P. V. Glybochko; Yu. G. Alyaev; L. M. Rapoport; D. G. Tsarichenko; E. G. Arzumanyan (Андрология и генитальная хирургия, 2014)
The article describes a novel technique of performing transurethral cystolithotripsy in gas (carbon dioxide) medium, and the results of its first usage in 30 patients with bladder stones, compared to transurethral cystolithotripsy in conventional liquid medium in 30 patients. Data analysis shows that the rate of stone destruction in gas media was 1.47 times higher in small (less than 10 g) stones and 2.3 times higher in large (more than 10 g) stones as compared to surgeries conducted in liquid media. Also, we concluded that our proposed technique is safe and has advantages when compared to conventional surgery in liquid media. This is absence of increased stone mobility, better visualization during surgery and higher economic efficacy (5 times on average).